Effect of Nettle (Urtica dioca L.) density on fiber yield and quality in a natural ecosystem under East Mediterranean conditions - Kakabouki, Ioanna; Zisi, Charikleia; Karydogianni, Stella; Priniotakis, George; Darawsheh, Mohammed K; Tselia, Zoi (Journal of Phytology, 2020)
Nettle (Urtica dioica L.), a new industrial crop, has been cultivated since the 12th century for its fibers. This study was conducted to specify the optimal density of plants in order to move from wild harvest to nettle cultivation. For the present study, sampling was performed in 21 different fields throughout Greece, during October 2018. The effect of nine different plant densities on several agronomic (plants height, leaf area and dry matter) and fiber quality (straw length, fiber percentage, yield, extension at break, strength, length, diameter) characteristics was determined. The higher fiber yield occurred at the lower density (4 plants m2), while the higher fiber diameter observed at the highest density (12 plants m2). Comparisons were performed at the 5% level of significance (p ≤ 0.05). According to our results, there have been negative correlations between plant density and certain agronomic and quality characteristics such as plant height and fiber length, hence the optimal density is about seven plants per m2.